Adult alcohol drinking and emotional tone are mediated by neutral sphingomyelinase during development in males - Kalinichenko, Liubov; Mühle, Christiane; Jia, Tianye; Anderheiden, Felix; Datz, Maria; Eberle, Anna-Lisa; Eulenburg, Volker; Granzow, Jonas; Hofer, Martin Jürgen; Hohenschild, Julia; Huber, Sabine; Kämpf, Stefanie; et al. (Cerebral Cortex, 2022)
Alcohol use, abuse, and addiction, and resulting health hazards are highly sex-dependent with unknown mechanisms. Previously, strong links between the SMPD3 gene and its coded protein neutral sphingomyelinase 2 (NSM) and alcohol abuse, emotional behavior, and bone defects were discovered and multiple mechanisms were identified for females. Here we report strong sex-dimorphisms for central, but not for peripheral mechanisms of NSM action in mouse models. Reduced NSM activity resulted in enhanced alcohol consumption in males, but delayed conditioned rewarding effects. It enhanced the acute dopamine response to alcohol, but decreased monoaminergic systems adaptations to chronic alcohol. Reduced NSM activity increased depression- and anxiety-like behavior, but was not involved in alcohol use for the self-management of the emotional state. Constitutively reduced NSM activity impaired structural development in the brain and enhanced lipidomic sensitivity to chronic alcohol. While the central effects were mostly opposite to NSM function in females, similar roles in bone-mediated osteocalcin release and its effects on alcohol drinking and emotional behavior were observed. These findings support the view that the NSM and multiple downstream mechanism may be a source of the sex-differences in alcohol use and emotional behavior.
CRIS-Team WoS Importer:2022-04-15
Keywords: neutral sphingomyelinase; osteocalcin; depression; alcohol; anxiety